Immunological evaluation of inactivated Newcastle disease vaccine depending on adjuvant composition - Chegrynets, A. I.; Saliy, O. O.; Sobko, I. A.; Krasinko, V. O. (Regulatory Mechanisms in Biosystems, 2021)
Newcastle disease is a global problem that is being recorded in most countries and also a serious obstacle to exchange of genetic material of poultry in various countries of the world. Control of the Newcastle disease comprises correct injection of efficacious vaccines so as to decrease or eliminate the clinical disease. Our goal was to perform comparative studies of the vaccines against Newcastle disease of water in oil type, the adjuvant being mineral oil mixed with emulsifiers (Span-80 and Tween-80) and ready-to-use adjuvant system (Montanide ISA 70), and study the impact of composition of adjuvant constituent on physical-chemical and immunogenic properties of inactivated vaccines. To reproduce virus-containing material and carried out titration of the viruses, we used chicken embryos free of pathogenic microflora. Aqueous phase for the preparation of emulsion-based vaccines of water in oil type consisted of antigen to Newcastle disease of La-Sota strain, manufactured by Biotestlab Ltd, and phosphate-saline buffer. To evaluate the effectiveness of the vaccine and induce immune response, we used 1-day old pathogen-free chickens, which were obtained from chicken embryos free of pathogenic microflora. As the positive control in the experiment, we used commercial vaccine. One-day chickens were divided into 3 groups (I, II, III) comprising 12 individuals each and one group (IV) consisting of 8 individuals as the control group with individual numeration. Chickens in groups I, II and III were divided into two subgroups (n = 8 and n = 4) to determine immunogenic efficiency and safety of the vaccine. Immunization was carried out through single subcutaneous injections in the region of the neck. To study immunogenic efficiency, the chickens were immunized with the dose of 0.1 mL (1 dose), and 0.2 mL (2 doses) to determine safety. After the immunization of 1-day old pathogen-free chickens with 0.1 mL dose, the obtained level of antibodies in the serum of vaccinated chickens on days 14, 21, 28, 35 and 42 after the vaccination indicated the ability of provoking the immune response to Newcastle disease at high level and safety of the vaccination for chickens. All the recipes of the examined series of the vaccines and the commercial vaccine produced appropriate level of viscosity according to the criterion equaling ≤ 200 mm2/s at Р <0.05, promoting fluidity of the vaccine and providing easier passage through the needle during the application. Both of the studied vaccines may be used in poultry farming for prophylaxis of Newcastle disease among chickens.